Pornografi dan Pornoaksi Dalam Perspektif Hadis - Najwah, Nurun (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
Issues on pornography and porno action have actually been circulated around since a long time, probably as early as human civilization developed. In Indonesia, however, pornography has become the centre of debates when a legal draft on anti pornography and porno action was socialized. There are pro and contra camps developed in respond to the issue and legal draft proposed by the DPR. This article attempts to elaborate the reported written traditions of the Prophet with regard to porn issues: in what ways and how deep did the Prophet say about pornography? As far as the author's research is concerned, she has no trace of any single hadis that directly addressing pornography or porn pictures in the same way the Prophet responded to other problems of his time through hadis. This article therefore seeks to discover how far the Prophet had appreciated graphic arts and how he had set certain behaviors that might lead to illicit sexuality. It is found that the Prophet had required that Muslims should observe several practices that will prevent them from falling into illegitimate sexual engagements, such as covering up the aurat (shame), two people sharing one blanket, and courtship in privacy. While giving such warnings, however, the Prophet did not explicitly set penalties to those who have transgressed the boundaries.